Growth maturity stage defines nutritional, anti-nutrients and functional food aspects of Moringa oleifera Lam. leaves - Saima Perveen; Saeed Akhtar; Dur-e-shahwar Sattar; Muhammad Qamar; Wisha Saeed; Mavra Amin; Tariq Ismail (Food Chemistry Advances)
This study evaluates nutritional composition and anti-nutrients profile of Moringa oleifera leaves across different growth stages aimed at identifying optimum harvest time to secure better dietary profile of the leaves. The results showed that physicochemical composition of mature leaves present a significantly (p ≤ 0.05) higher level of protein (23.71 %), fiber (28.26 %), and fat (13.26 %) with a relatively lower amount of caloric energy (271.93 kcal) as compared to those observed in tender and young leaves. Progressive reduction (p ≤ 0.05) was noticed in anthocyanin (31.96 to 14.31 mg/100 g), chlorophyll b (72.83 to 45.16 mg/100 g) and lycopene (22.67 to 11.94 mg/100 g) content of M. oleifera leaves with advancing growth stage. Growth stages depicted an increase in the β-carotene and chlorophyll A contents of M. oleifera leaves. Higher phenolics yield and antioxidant activity of the leaves extracts was recorded for methanolic extracts. Advanced stage of leaves maturity anticipated highest level of total phenolics i.e., 49.02 mg GAE/g, total flavonoids content i.e., 52.96 mg QE/g and flavonols (28.83 mg QE/g). Comparatively higher concentrations of alkaloids (2.74 g/100 g), saponin (3.82 g/100 g), oxalates (2.43 g/100 g), tannin (0.837 g/100 g), and phytic acid (1.94 g/100 g) content were recorded in mature leaves. Harvesting M. oleifera leaves at peak maturity enhances their protein, dietary fiber, micronutrient, and phytochemical content. However, mature leaves may also accumulate higher levels of anti-nutrients like oxalates and phytates, which can interfere with mineral absorption.